2007
DOI: 10.1101/gad.1580507
|View full text |Cite
|
Sign up to set email alerts
|

Ntr1 activates the Prp43 helicase to trigger release of lariat-intron from the spliceosome

Abstract: DEAD/H-box NTPases remodel the spliceosome at multiple steps during the pre-mRNA splicing cycle. The RNA-dependent NTPase Prp43 catalyzes dissociation of excised lariat-intron from the spliceosome, but it is unclear how Prp43 couples the energy of ATP hydrolysis to intron release. Here, we report that activation of Prp43's inherently feeble helicase activity by the splicing factor Ntr1 is required for lariat-intron release. Lethal Prp43 mutants T384A and T384V, which are active for ATP hydrolysis and fail to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
216
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(226 citation statements)
references
References 44 publications
7
216
1
2
Order By: Relevance
“…For example, Tsai et al (2007) have shown in a yeast two-hybrid assay that Ntr2 binds to Brr2, and, as Brr2 also binds to U5 snRNP and Prp43 binds to Ntr1, this would suggest a functional link among these components and the possibility that the formation of this complex would stimulate the helicase activity of Prp43 (Tanaka et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tsai et al (2007) have shown in a yeast two-hybrid assay that Ntr2 binds to Brr2, and, as Brr2 also binds to U5 snRNP and Prp43 binds to Ntr1, this would suggest a functional link among these components and the possibility that the formation of this complex would stimulate the helicase activity of Prp43 (Tanaka et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Yeast Prp43 interacts with its cofactors, Ntr1 (also called Spp382) and Ntr2, forming the NTR complex (Tsai et al 2005;Boon et al 2006). Ntr2 forms a tight complex with Ntr1, while Ntr1 interacts with Prp43 through its G-patch domain (Tsai et al 2005;Tanaka et al 2007). The latter interaction is crucial for the stimulation of Prp43's otherwise weak RNA helicase activity, which is essential for IL release (Tanaka et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the long branch site to 3′ splice site distance in the telomerase RNA intron may impede exon ligation by rendering the substrate sensitive to Prp22p-mediated rejection and Prp43p-mediated discard, thereby liberating the 3′ processed telomerase RNA. Finally, given the established role of Ntr1p/Spp382p in the activation of Prp43p (20), additional regulatory factors could target Prp43p to effectively modulate the partitioning of a substrate between discard and productive splicing and thereby to regulate this stage of RNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas nuclear turnover may simply compete with splicing, cytoplasmic turnover implies that the spliceosome can dissociate a suboptimal substrate. After splicing, spliceosome disassembly and the dissociation of an optimal, excised intron require Ntr1p/Spp382p, Ntr2p, and the DEAH box ATPase Prp43p (20)(21)(22)(23)(24)(25), which also functions in the processing of pre-rRNA and histone pre-mRNA (26)(27)(28)(29). Interestingly, mutations in PRP43 and NTR1/SPP382 suppress mutations in the spliceosome assembly factors PRP38 as well as PRP8, and Ntr1p/Spp382p associates in vitro with stalled spliceosomes that retain the lariat intermediate but lack the 5′ exon, hinting that the spliceosome discards intermediates by a mechanism that parallels the mechanism for discarding an optimal, excised intron product (30).…”
mentioning
confidence: 99%